2019
DOI: 10.1177/1933719118770550
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Phthalate and Personal Care Products Exposure Alters Extracellular Placental miRNA Profile in Twin Pregnancies

Abstract: Prenatal exposure to endocrine-disrupting chemicals (EDCs) exerts both short- and long-term adverse effects on the developing fetus. However, the mechanisms underlying these effects have yet to be uncovered. Maternal-fetal signaling is mediated in part by signaling molecules (eg, microRNAs [miRNAs]) contained in extracellular vesicles (EVs) that are released by the placenta into the maternal circulation. We investigated whether maternal exposure to the EDCs phthalates and personal care products alters the miRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 46 publications
1
20
1
Order By: Relevance
“…However, a recent small ( n = 10 twin pregnancies) study assessed 3 circulating placentally sourced miRs (identified a priori in a literature search) in maternal plasma to assess associations with phthalates and phenols. Authors reported that MBzP, but not other phthalates, was positively associated with miR_518e, and that several phenols ( Table 2 ) were positively or negatively associated with the 3 measured miRs [ 93 ]. These data are promising, and should be followed up by analyses in larger cohorts, assessing a wider array of placenta-specific miRs.…”
Section: Epigenetic Consequences Of Bpa or Phthalate Exposures In Thementioning
confidence: 99%
“…However, a recent small ( n = 10 twin pregnancies) study assessed 3 circulating placentally sourced miRs (identified a priori in a literature search) in maternal plasma to assess associations with phthalates and phenols. Authors reported that MBzP, but not other phthalates, was positively associated with miR_518e, and that several phenols ( Table 2 ) were positively or negatively associated with the 3 measured miRs [ 93 ]. These data are promising, and should be followed up by analyses in larger cohorts, assessing a wider array of placenta-specific miRs.…”
Section: Epigenetic Consequences Of Bpa or Phthalate Exposures In Thementioning
confidence: 99%
“…Placenta-derived EV-miRNAs are released by the placenta into the maternal circulation during pregnancy, and are responsible for regulating the endocrine environment to facilitate pregnancy and fetal growth (Mitchell et al, 2015). An exploratory study revealed that maternal exposure to phthalates and parabens can alter the profile of circulating EV-miRNAs (Zhong et al, 2019). miR-518e is highly expressed in women with elevated urinary levels of monobenzyl phthalate and methyl paraben.…”
Section: Micrornas and Placentamentioning
confidence: 99%
“…miR-518e is highly expressed in women with elevated urinary levels of monobenzyl phthalate and methyl paraben. miR-373-3p had the lowest expression in women exposed to high levels of methyl paraben while miR-543 showed significant downregulation in women with high levels of paraben metabolites (Zhong et al, 2019). miR-518e, a member of the C19MC family is restricted to the placenta and the reproductive system and has high expression levels in the placentas of women having preeclampsia (Yang et al, 2015;Vashukova et al, 2016).…”
Section: Micrornas and Placentamentioning
confidence: 99%
“…In another study, blood and urine from women pregnant with uncomplicated, healthy twins were analyzed for the correlation between prenatal phthalate exposure and miRNA profiles in extracellular vesicles (EV-miRNA) in maternal blood [ 88 ]. The researchers evaluated 20 placental-derived EV-miRNAs circulating in maternal plasma in relation to 13 phthalates and eight other chemicals used in plastics.…”
Section: Environmental Toxicantsmentioning
confidence: 99%
“…The researchers evaluated 20 placental-derived EV-miRNAs circulating in maternal plasma in relation to 13 phthalates and eight other chemicals used in plastics. Only MBzP displayed a positive association with miR-518 [ 88 ]. MBzP is a metabolite formed from butyl benzyl phthalate [ 89 ], and seems to have a potent effect on placental miRNA expression, specifically those implicated in preeclampsia.…”
Section: Environmental Toxicantsmentioning
confidence: 99%